"From Patient to Survivor": Women's Experience With Breast Cancer After 5 Years. Issue 3 (May 2016) - Fang, Su-Ying; Lee, Kuo-Ting
Abstract : Background: Women who have survived breast cancer for 5 years without recurrence are not subject to active follow-up because of limited resources. Their life experiences more than 5 years subsequent to diagnosis and treatment are unknown. Objective: The aim of this study was to understand the life experiences and care needs of women who have survived breast cancer for more than 5 years in Taiwan. Methods: A purposive sampling was used. Women diagnosed with breast cancer more than 5 years previously and without recurrence were recruited in this study. The interviews were conducted in a comfortable and convenient place decided by the participants. The interviews were converted into transcripts and analyzed using content analysis. Results: Thirteen women participated in this study whose ages were between 48 and 72 years. Five main themes were identified: (1) fear of recurrence, with women attempting to use ways to reduce recurrence, including dependence on drugs, desire for information, and promoting health; (2) hoping for alleviation of adverse effects; (3) seeking a body image; (4) expectations for the patient-physician relationship; (5) concerns of a mother; and (6) positive thinking. Conclusions: Taiwanese women with post 5-year breast cancer survival continue to have physiological and emotional needs. They long for attention and care from their healthcare team. Implications for Practice: It is pivotal to formulate a care plan suitable for 5-year-plus survivors of breast cancer and to assist them in gaining an understanding of the latest treatments and self-care information. It is crucial that nurses play a greater role in caring for long-term survivors.